Epididymal metastasis from prostate adenocarcinoma: An unusual and challenging diagnosis suspected in gallium-68 prostate-specific membrane antigen-positron emission tomography/computed tomography and histologically confirmed - Santos-Lopes, S (2017)
A few cases of prostate adenocarcinoma (PCa) metastases to the epididymis have been documented in literature. We report a case of a 69-year-old man with a left epididymal metastasis, 6 years after radical prostatectomy and adjuvant radiation therapy for PCa. Although he developed biochemical recurrence, only gallium-68 prostate-specific membrane antigen-positron emission tomography/computed tomography revealed high uptake in the left testis and retrovesical space. An unrecognized painless firm nodule was palpable on the left epididymis. Radical orchiectomy was performed, and histopathological examination confirmed PCa metastasis located in the epididymis. To the best of our knowledge, this is the 27th reported case of epididymal metastasis from PCa.